ANALISIS DAN EVALUASI KONTAMINASI LOGAM BERAT DI SEDIMEN, AIR DAN RUMPUT LAUT Euchema Cottoni Di KOTA TARAKAN - Ratno Achyani; Encik Weliyadi; Rismawati . (Jurnal Harpodon Borneo, 2013)
The purpose of this study is to provide information about the existence, type, amount and concentration of heavy metals in waters and sediments and its accumulation in seaweed Euchema Cottonii at Amal waters Tarakan City. in the waters has found two types of heavy metal, cadmium (Cd) and nickel (Ni) in water and sediments. In Euchema Cottoni seaweed has found 2 types of heavy metals, Copper (Cu) and Iron (Fe) when the seedling and 4 types of heavy metals during harvest is Copper (Cu), iron (Fe), manganese (Mn) and nickel (Ni). Concentrations of heavy metals in the waters of cadmium from 0.005 to 0.007 mg/l and nickel 0.064 to 0.084 mg/l. Concentrations of heavy metals in the sediment are cadmium 0.068 mg/l and nickel 0.175 mg/l. Concentrations of heavy metals in seaweed Euchema Cottoni when seedlings are Copper 1.91 mg/l, iron 86.64 mg/l. Concentrations of heavy metals in seaweed Euchema Cottoni at harvesting the Copper 4.03 mg/l, manganese 151.25 mg/l, iron 0.97 mg/l and nickel 16.6 mg/l.  Keyword: heavy metals, waters, sediments, Euchema Cottonii.